Implementation of European cohesion policy at the sub-national level: Evidence from beneficiary data in Eastern Germany - Bianka Dettmer; Thomas Sauer (Ernst-Abbe-Hochschule Jena, Fachbereich Betriebswirtschaft, 2016)
Regional governments' discretion in allocating structural funds is mainly limited by the competences of the Commission to control implementation and fiscal activities of decentralized governments. In this paper, we analyse implementation of ERDF funds in Eastern Germany in the financial perspective 2007 to 2013 to show how allocation of the funds follows the objectives formulated in the programmes. We find that less rural regions and some economic sectors benefit by more than others. A few beneficiaries control the highest share of the funds. This indicates that political economy forces in the allocation process may benefit well organised groups.
Keywords: H5; H7; R11; 330; EU regional policy; structural funds; redistribution; implementation; beneficiaries; multi-level-governance; programming period 2007-13